Analysis of the suitability of floating net cage cultivation land based on environmental carrying capacity in Apal Village, Banggai Islands Regency - Prayitno Kumeria, Toto; Koniyo, Yuniarti; Juliana (Universitas Malikussaleh, 2025)
This study aims to analyze the carrying capacity of the aquatic environment and the factors that affect the development of Floating Net Cage (KJA) cultivation in Apal Village, Liang District, Banggai Islands Regency. The approach used is quantitative with a field survey method, including the measurement of physical, chemical, and biological parameters of the waters as well as social, economic, legal, and institutional analysis of coastal communities. Physico-chemical data were analyzed descriptive-comparatively based on the Decree of the Director General of PRL No. 55 of 2023, while socio-economic factors were analyzed using multiple linear regression with the help of SPSS 26 software. The results of the study show that the condition of land suitability varies between stations; temperature and general current are still appropriate, but salinity and nitrates exceed thresholds; Ammonia is in the highly appropriate category (S1), while phosphate is high at some points (N). Plankton diversity is moderate (H' 2,232–2,980), indicating fairly good ecosystem stability. Socially, economically, and institutionally, social and economic factors have a positive effect on the carrying capacity of the environment although it is not significant, while institutions have a negative effect due to weak coordination and supervision. In conclusion, the waters of Apal Village still have the potential for sustainable KJA development, but mitigation of high salinity, nutrient load control, and institutional strengthening are needed so that the carrying capacity of the environment is maintained. Keywords: Economic; Environmental Carrying Capacity; Floating Net Cages; Social; Water Quality